Promoting neuroplasticity for functional restoration after SCI - Field-Fote, Edelle (Henry Stewart Talks, 2011)
Neuroplasticity, Synaptic efficacy, Neural mechanisms of plasticity, Improving hand function after SCI, Improving walking function and spinal reflex modulation after SCI, Promoting adaptive neuroplasticity, Update interview: Clinically accessibility is a key to the value of neuromodulation, Update interview: Transcranial direct current stimulation, Update interview: Transcutaneous spinal stimulation, Update interview: Questions remain about dose of intervention, Update interview: Neuromodulation is dependent on concurrent training, Update interview: Potential for neuroplasticity persists long after injury, Update interview: Continued practice is needed to retain gains
Updated at 2021/03/15